Phylogeography and biological characterization of H12N2 virus isolated from whooper swan in Central China - Ren, Pengfei; Gao, Zhen; Li, Xing; Tang, Jiao; Li, Pei; Huang, Zhonglin; Guo, Jinchi; Cui, Pengfei; Jin, Lin; Li, Junping; Liang, Libin (Frontiers in Microbiology, 2025)
Wild birds and waterfowl serve as the natural reservoirs of avian influenza viruses (AIVs). When AIVs originating from wild birds cross species barriers to infect mammals or humans, they pose a significant threat to public health. The H12 subtype of AIVs primarily circulates in wild birds, with relatively few isolates reported worldwide, and the evolutionary and biological characteristics of H12 subtype AIVs remain largely unknown. In this study, we analyzed the spatiotemporal distribution of H12 subtype AIVs worldwide and conducted a comprehensive investigation into the evolutionary and biological characteristics of an H12N2 virus isolated from a whooper swan in Central China. Phylogenetic analysis revealed that the H12N2 isolate belongs to the Eurasian lineage, with its HA gene likely originating from a duck-derived H12N5 virus and its NA gene potentially derived from an H9N2 virus, indicating that it is a complex reassorted virus. Animal experiments in domestic ducks and chickens demonstrated that the virus replicates at low levels in the respiratory tract of poultry and exhibits moderate horizontal transmission in ducks. However, it is capable of efficient horizontal transmission in chickens. Mouse infection experiments revealed that the virus could be detected in the nasal turbinates and lungs of mice, indicating that the H12N2 virus can infect mice without prior adaptation. In vitro studies revealed that the virus replicates efficiently in MDCK cells, with significantly higher titers than those in DF1 cells. These findings, combined with the mouse infection results, suggest that the H12N2 virus poses a potential risk of mammalian infection. This study provides valuable insights regarding the characteristics of the H12N2 virus and highlights the importance of ongoing surveillance and risk assessment of AIVs originating from wild birds.